Refining Process-oriented Guided Inquiry Learning for Chemistry Students in an Academic Development Programme. Issue 2 (4th May 2019) - Mundy, Christine; Potgieter, Marietjie
Abstract : In this study, action research was used over two years to refine the implementation of process-oriented guided inquiry learning for chemistry students in an academic development programme at a research-intensive South African university. Students' responses to guided inquiry were collected based on a three-pillar framework underpinned by cognitive load theory and the information processing model. A mixed methods approach was used to gather data including observations, questionnaire responses, focus group interviews and student assessment results. The findings were exhibited year by year using the analysis tool, 'joint displays'. Findings from the first year of study highlighted student difficulty with factors contributing to extraneous load such as social dynamics, worksheet layout and time required. Revisions addressed these areas of difficulty in the second year with positive results in terms of student behaviour and achievement. Analysis of Year 2 findings led to several recommendations for further guided inquiry revisions to serve novice students in the context of an academic development programme: prior knowledge should be activated to mitigate cognitive overload, relevant language should replace foreign terms to sensitise the perception filter and more explicit scaffolding could be embedded to enrich the student's germane cognitive load during processing.